2004
DOI: 10.1021/ac0495743
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Droplets of Alternating Composition in Microfluidic Channels and Applications to Indexing of Concentrations in Droplet-Based Assays

Abstract: For screening the conditions for a reaction by using droplets (or plugs) as microreactors, the composition of the droplets must be indexed. Indexing here refers to measuring the concentration of a solute by addition of a marker, either internal or external. Indexing may be performed by forming droplet pairs, where in each pair the first droplet is used to conduct the reaction, and the second droplet is used to index the composition of the first droplet. This paper characterizes a method for creating droplet pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
263
1
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 305 publications
(283 citation statements)
references
References 40 publications
(96 reference statements)
7
263
1
8
Order By: Relevance
“…It can be seen from Fig. 4(b) that the grid independence is achieved when the droplets form in ADF regime, observed experimentally by Zheng et al 13 in the same flow condition. The droplet diameter obtained in present study lies within the range between the lower and upper bounds reported, 13 showing quantitative agreements with experiments.…”
Section: B Code Validationsupporting
confidence: 72%
See 4 more Smart Citations
“…It can be seen from Fig. 4(b) that the grid independence is achieved when the droplets form in ADF regime, observed experimentally by Zheng et al 13 in the same flow condition. The droplet diameter obtained in present study lies within the range between the lower and upper bounds reported, 13 showing quantitative agreements with experiments.…”
Section: B Code Validationsupporting
confidence: 72%
“…The four regimes, namely, merging (MDF), alternating (ADF), alternating-jetting, and jetting, experimentally observed by Zheng et al 13 are reproduced for the first time by numerical simulations in the present study, which in turn allow comprehensive parametric study not available in previous reports. Here, extensive numerical study is performed to investigate the effect of capillary number (10 À3 Ca 0.5), Reynolds number (7.4 Â 10 À4 Re 0.37), and channel width ratio (k ¼ 0.5, k ¼ 1.0, and k ¼ 1.5).…”
Section: A Geometry Effects and Adf Phenomenonsupporting
confidence: 70%
See 3 more Smart Citations